Sediment inputs from retrogressive thaw slumps drive algal biomass accumulation but not decomposition in Arctic streams, NWT. (10th July 2018) - Levenstein, Brianna; Culp, Joseph M.; Lento, Jennifer
Abstract: Increasing rates of precipitation and higher air temperatures have increased the size and frequency of retrogressive thaw slumps—large depressions of thawed permafrost that form on the landscape—in north‐western Canada. Many of these thaw slumps flow into nearby stream systems, leading to increased sediment, solute and nutrient loads. We evaluated the impacts of retrogressive thaw slumps on measurements of algal biomass accumulation and decomposition of organic materials in streams in the Peel Plateau, Northwest Territories. We predicted that increased sediment loads from thaw slumps would decrease algal standing stock and decomposition in thaw slump‐impacted streams, overriding the potential positive effects of increased nutrient concentrations. Chl‐ a measurements were obtained as a proxy for algal standing stock from sites upstream and downstream of thaw slumps by performing algae scrapes and deploying artificial substrates in 2014. Cotton strips were deployed at upstream and downstream sites in 2013 and 2014, and tensile strength was measured to assess breakdown. Grab water samples were taken to measure physical and chemical parameters at each site. Thaw slumps increased total suspended solids, but not dissolved nutrients at downstream sites. Our results indicated a significant negative relationship between Chl‐ a and total suspended solids. Decomposition indicated a negative relationship with total suspended solids, but displayed much stronger positive relationships with temperature, pH and dissolved phosphorus. Our findings indicated that total suspended solids were a stronger driver of change in thaw slump‐impacted stream reaches than nutrients, although nutrients may be more influential during the initiation of thaw slump disturbances. Algal biomass accumulation was found to be more sensitive to thaw slump impacts than decomposition, which may lead to a functional and structural shift in favour of allochthonous‐based food webs over autochthonous ones at thaw slump‐impacted stream reaches.